Postprandial glycemia, insulinemia, and satiety responses in healthy subjects after whole grain rye bread made from different rye varieties. 1 - Rosén, Liza A H; Östman, Elin M; Shewry, Peter R; Ward, Jane L; Andersson, Annika A M; Piironen, Vieno; Lampi, Anna-Maija; Rakszegi, Marianne; Bedö, Zoltan; Björck, Inger M E (Journal of agricultural and food chemistry, 2011)
Rye products typically induce low insulin responses and appear to facilitate glucose regulation. The objective of this study was to investigate differences in postprandial glucose, insulin, and satiety responses between breads made from five rye varieties. Breads made from whole grain rye (Amilo, Rekrut, Dankowski Zlote, Nikita, and Haute Loire Pop) or a white wheat bread (WWB) were tested in a randomized cross-over design in 14 healthy subjects (50 g available starch). Metabolic responses were also related to the composition of dietary fiber and bioactive compounds in the breads and to the rate of in vitro starch hydrolysis. The Amilo and Rekrut rye breads induced significantly lower insulin indices (II) than WWB. Low early postprandial glucose and insulin responses (tAUC 0-60 min) were related to higher amounts of caffeic, ferulic, sinapic, and vanillic acids in the rye breads, indicating that the phenolic acids in rye may influence glycemic regulation. All rye breads induced significantly higher subjective feelings of fullness compared to WWB. A low II was related to a higher feeling of fullness and a lower desire to eat in the late postprandial phase (180 min). The data indicate that some rye varieties may be more insulin-saving than others, possibly due to differences in dietary fiber, rate of starch hydrolysis, and bioactive components such as phenolic acids.